Talajvizsgálatok a Keszthelyi- hegységben - Horváth Gergely (2018)
In my thesis I deal with the examination of earth boring and soil profiles performed in the Keszthely Mountains. From pedology aspect, I am searching the reasons of the deterioration of the health status of forest resources started in 2012. During my work, I researched the data of salvage logging from 2012 to 2016. Based on the samples taken from soil profiles, I carried out laboratory tests and analyzed the results. I have tried to make suggestions on the tree species that can be applied to the salvage logged locations.